(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Digital transformation has become a key driver of competitiveness for micro, small, and medium enterprises (MSMEs), particularly within rural, tourism-based economies. This study examines the extent of AI marketing utilization and the level of entrepreneurial behavior among MSMEs in Bojong Rangkas Tourism Village, Indonesia. Using a descriptive quantitative approach, data were collected through a survey of 39 MSMEs operating in the village. The findings indicate that AI marketing and digital technology adoption are relatively high (67.2%), while entrepreneurial behavior remains at a moderate level (58.8%). Key strengths include the widespread use of online payment systems (75%) and active engagement with digital marketplaces (68.8%). However, weaknesses persist in human resource development, with training activities reported at only 50%. The study further identifies a conceptual linkage between digital adoption and the strengthening of entrepreneurial behavior, particularly in collaboration, organizational clarity, and innovation. These results highlight the need for integrated capacity-building programs that combine AI-based marketing skills with the development of entrepreneurial competencies.